2020
DOI: 10.3390/nu12113444
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-Induced Intestinal Microbiota Shift Following Two Types of Short-Term High-Fructose Dietary Phases

Abstract: High consumption of fructose and high-fructose corn syrup is related to the development of obesity-associated metabolic diseases, which have become the most relevant diet-induced diseases. However, the influences of a high-fructose diet on gut microbiota are still largely unknown. We therefore examined the effect of short-term high-fructose consumption on the human intestinal microbiota. Twelve healthy adult women were enrolled in a pilot intervention study. All study participants consecutively followed four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 78 publications
(63 reference statements)
3
45
0
Order By: Relevance
“…Erysipelatoclostridium is a butyrate-producing bacterium [ 48 ]. It has been discovered to be enhanced in DSS-treated colitis mice [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Erysipelatoclostridium is a butyrate-producing bacterium [ 48 ]. It has been discovered to be enhanced in DSS-treated colitis mice [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…High fructose corn syrup supplemented foods resulted in destruction of beneficial butyrate producing gut bacteria and problematic microbial metabolism of host lipids. In contrast, naturally occurring fructose as part of a fruit-based diet appeared to produce an opposite beneficial effect [114].…”
Section: Tastementioning
confidence: 99%
“…A final point is the effect of high fructose corn syrup specifically on the human microbiome. In a study by Beisner et al [114], researchers found that different formulation of foods containing fructose resulted in different gut microbiome compositions and metabolism. High fructose corn syrup supplemented foods resulted in destruction of beneficial butyrate producing gut bacteria and problematic microbial metabolism of host lipids.…”
Section: Tastementioning
confidence: 99%
“…A final point is the effect of high fructose corn syrup specifically on the human microbiome. In a study by Beisner et al [ 114 ], researchers found that different formulation of foods containing fructose resulted in different gut microbiome compositions and metabolism. High fructose corn syrup supplemented foods resulted in the destruction of beneficial butyrate producing gut bacteria and problematic microbial metabolism of host lipids.…”
Section: Who Behavioral Modification #1: Eat a Healthy Diet (In Spite Of The Microbiota-driven Sense Control)mentioning
confidence: 99%